2022
DOI: 10.7189/jogh.12.05051
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine and health access inequalities during the COVID-19 pandemic

Abstract: Background During the COVID-19 pandemic, health systems rapidly introduced inhome telehealth to maintain access to care. Evidence is evolving regarding telehealth's impact on health disparities. Our objective was to evaluate associations between socioeconomic factors and rurality with access to ambulatory care and telehealth use during the COVID-19 pandemic. MethodsWe conducted a retrospective study at an academic medical centre in midwestern United States. We included established and new patients who received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
2
6
1
Order By: Relevance
“…Our investigation revealed a noteworthy trend wherein the utilization of telemedicine services in rural regions during the COVID-19 pandemic exhibited a proportional decrease as the degree of urbanization diminished (in order of metropolitan central cities, large fringe metropolitan cities, medium and small metropolitan cities, and rural areas). Multiple scholarly inquiries have been dedicated to scrutinizing the disparities in telehealth utilization that manifested during the initial phases of the COVID-19 pandemic, 26,27 and these results are consistent with our outcomes. The findings from prior studies consistently highlighted a discernible pattern: older individuals, non-white populations, and those covered by Medicaid or lacking insurance coverage in rural populations demonstrated a reduced likelihood of engaging in telehealth consultations, in contrast to their counterparts who were white, English-speaking, and possessed commercial insurance.…”
Section: Discussionsupporting
confidence: 85%
“…Our investigation revealed a noteworthy trend wherein the utilization of telemedicine services in rural regions during the COVID-19 pandemic exhibited a proportional decrease as the degree of urbanization diminished (in order of metropolitan central cities, large fringe metropolitan cities, medium and small metropolitan cities, and rural areas). Multiple scholarly inquiries have been dedicated to scrutinizing the disparities in telehealth utilization that manifested during the initial phases of the COVID-19 pandemic, 26,27 and these results are consistent with our outcomes. The findings from prior studies consistently highlighted a discernible pattern: older individuals, non-white populations, and those covered by Medicaid or lacking insurance coverage in rural populations demonstrated a reduced likelihood of engaging in telehealth consultations, in contrast to their counterparts who were white, English-speaking, and possessed commercial insurance.…”
Section: Discussionsupporting
confidence: 85%
“…13 Datta et al found lower rates of telehealth utilization in commercially insured patients (compared to Medicare or Medicaid) and older age patients; higher rates were seen in female patients. 14 We did not find strong associations between provider attributes and telehealth adoption. Our analysis showed that patients with certain diagnoses were more prone than their counterparts to have a televisitdnotably prostate cancer, stone, elevated PSA, hypogonadism, OAB, and erectile dysfunction.…”
Section: Discussioncontrasting
confidence: 54%
“…Research has consistently found that older individuals are less likely to use telehealth. 9 , 23 , 29 …”
Section: Discussionmentioning
confidence: 99%